(untitled) (Bangladesh Journal of Botany, 2021)
The study was conducted to estimate the biomass and carbon stock in the dominant tree species of the Kaptai National Park of Bangladesh. A total of 77 tracks and 308 plots were selected and all trees in each plot were measured to estimate the biomass following allometric equations. There were planted stand of Acacia auriculiformis, Dipterocarpus turbinatus, Gmelina arborea, Lagerstroemia speciosa, Swietenia macrophylla and Tectona grandis. Biomass and carbon stocks of these corresponding tree species were 35.03, 73.86, 23.52, 30.16, 44.49, and 42.67 mg/ha. The highest carbon stock per tree was in D. turbinatus (372.19 kg C/tree), followed by S. macrophylla (226.49 kg C/tree), T. grandis (215.06 kg C/tree), A. auriculiformis (176.56 kg C/tree), L. speciosa (151.19 kg C/tree) and G. arborea (118.54 kg C/tree), respectively. The findings of the study will be helpful for the estimation of carbon stocks in the forests of Bangladesh. Bangladesh J. Bot. 50(2): 365-371, 2021 (June)